Effect of Facedown vs Non-Facedown Position on Macular Hole Closure after Surgery - Shamshad Ali, Muhammad Hamza Shahid, Muhammad Shakil, Ayman Shahzad, Khawaja Mohsin Ihsan, Khalid Waheed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Internal Limiting Membrane (ILM) peeling with Gas tamponade after Pars Plana vitrectomy is routinely done in macular hole surgery. After the procedure, a face-down position (FDP) is advised to the patients to promote macular hole closure by pushing the bubble of Gas against the posterior pole. However, elderly patients and those with medical comorbidities may feel uncomfortable in FDP. A few post-operative complications may also be caused by it. So, the aim of this study is to compare and evaluate the role of postoperative non-face-down position (nFDP) and FDP on the macular hole closure rate after PPV with ILM peeling. Patients and methods: 20 phakic eyes of 20 patients, with idiopathic full-thickness macular holes, underwent vitrectomy, with dye-assisted peeling of the ILM and 14% perfluoro propane gas. Patients were divided randomly into two groups; face down position (FDP, posturing group) or non face down (nFDP, non-posturing group) for 7 days. Main focus was to see anatomical hole closure till 7 days postoperatively. Results: Macular holes closed in 10 of 10 eyes in the posturing (FDP) group and in 9 out of 10 in the non-posturing group (nFDP) seven days after the surgery. Chi-square test was applied to see the association between macular hole closure of patients with / without face down position. It was observed that macular hole closure was less likely to be associated with posturing (X2= 1.2, p-value= 0.549) while it was likely to be associated with size of macular hole (X2= 15.9, p-value= 0.001). In a sub-group analysis according to the size, all the macular holes smaller than 490 µm closed regardless of posturing. While holes larger than 490 µm were not closed in nFDP position. Conclusion: Post-operative face-down position has no statistically significant effect on macular hole closure in comparison to non-face down positioning. Keywords: Macular hole (MH), Face down position (FDP), Posturing, Closure rate, Randomized controlled Trials (RCTs)